2019
DOI: 10.1111/1365-2664.13502
|View full text |Cite
|
Sign up to set email alerts
|

Alien species spreading via biofouling on recreational vessels in the Mediterranean Sea

Abstract: 1. Despite the Mediterranean being both a hotspot for recreational boating and for non-indigenous species (NIS), no data currently exists on the recreational boating sector's contribution to the spread of NIS in this Sea.2. To improve the basis for management decisions, a wide-scale sampling study on the biofouling communities of recreational vessels and marinas was undertaken.Specifically, we surveyed over 600 boat owners and sampled the same boat hulls for NIS in 25 marinas across the Mediterranean, from Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 36 publications
4
50
0
Order By: Relevance
“…Immigration, from farms or rocky reefs, could result from the transport of spores by water currents, from drifting thalli detached from their substrate by storms or human activities (Sliwa et al 2006), or by recreational vessels (South et al 2017, Ulman et al 2019. Although spores only remain viable for a short period of time (1-2 days, Saito (1975a)), the high speed tidal currents in the bay of Morlaix, particularly during spring tides (up to 0.75 m/s in the vicinity of the marina), could carry spores and drifting thalli from nearby rocky reefs to the marina.…”
Section: Spill-back Effects Are Followed By a Shift Towards A Self-sumentioning
confidence: 99%
See 1 more Smart Citation
“…Immigration, from farms or rocky reefs, could result from the transport of spores by water currents, from drifting thalli detached from their substrate by storms or human activities (Sliwa et al 2006), or by recreational vessels (South et al 2017, Ulman et al 2019. Although spores only remain viable for a short period of time (1-2 days, Saito (1975a)), the high speed tidal currents in the bay of Morlaix, particularly during spring tides (up to 0.75 m/s in the vicinity of the marina), could carry spores and drifting thalli from nearby rocky reefs to the marina.…”
Section: Spill-back Effects Are Followed By a Shift Towards A Self-sumentioning
confidence: 99%
“…These marine urban habitats are considered as invasion hubs promoting the spread of NIS towards natural habitats (i.e., spill-over effects, Airoldi et al 2015;Bulleri, Chapman 2010). Recreational vessels, neglected for a long time, are indeed increasingly recognized as vectors transporting introduced species over a large range of distances (Clarke Murray et al 2011, Mineur et al 2008, Ulman et al 2019. Once marine NIS are established, eradicating them proves to be difficult and cost-inefficient in most cases (Ojaveer et al 2015;Simberloff et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study across 50 marinas showed Hydroides elegans (Haswell, 1883) to be present in 66%, Hydroides dirampha Mörch, 1863 in 32% and Ficopomatus enigmaticus (Fauvel, 1923) in 14% of them (Ulman et al 2019a). Serpulids were the most common family in boat hull biofouling communities, with H. elegans found on 71% (N=418) of the hulls and all serpulids combined accounting for over one-third of NIS records in relative abundance (Ulman et al 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…International regulations and codes of practice for international ships’ ballast water and aquaculture have greatly reduced the risk of new invasions via these vectors (Williams et al., 2013). However, biofouling of ships and boats is largely unregulated and remains a concern for primary and secondary invasions (Briski et al., 2012; Davidson, Scianni, Minton, & Ruiz, 2018; Ulman et al., 2019); thus, new invaders are likely to come from biofouling communities such as those modelled here. Some nations impose biosecurity measures such as biofouling compliance regulations for incoming vessels (Davidson et al., 2018; Ministry for Primary Industries, 2018), as well as trade bans on high impact invaders, albeit with mixed success of the latter (Patoka et al., 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Clarke Murray et al., 2011; Simkanin, Davidson, Falkner, Sytsma, & Ruiz, 2009; Ulman et al., 2019), movements of maritime structures such as oil rigs and docks (Iacarella, Davidson, & Dunham, 2019) and aquaculture translocations (Haydar & Wolff, 2011). Ship and boat traffic is a particularly strong vector within regions owing to the large number of vessels and their frequency of movements (as shown here; Iacarella, Burke, et al, 2020), the entrainment potential in biofouling, ballast and bilge water (Clarke Murray et al., 2011; Fletcher et al., 2017; Ulman et al., 2019) and the lack of regulatory oversite within domestic waters (Briski, Wiley, & Bailey, 2012; Simkanin et al., 2009). Comprehensive risk assessments at the species and MPA level would need to consider self‐dispersal capability and other vectors and source locations (Iacarella, Burke, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%